Chelate setting of alkali ion substituted calcium phosphates. Issue 8 (September 2015) - Sheikh, Zeeshan; Geffers, Martha; Christel, Theresa; Barralet, Jake E.; Gbureck, Uwe
Abstract: Ca2 KNa(PO4 )2 is an alkali substituted calcium orthophosphate that stimulates osteoblast growth, shows excellent biocompatibility both in vitro and in vivo and is biodegradable under in vivo conditions. We report the development and assessment of the physico-chemical properties of Ca2 KNa(PO4 )2 cements which set by a chelating reaction with phytic acid. This was beneficial to avoid formation of low soluble hydroxyapatite during setting and in vitro ageing in PBS. The concentration of phytic acid used for cement setting was found to have an inverse effect on mechanical properties. Cements with lower concentration of phytic acid had higher compressive strengths, but lower degradation speed in comparison to the higher concentration acid cements. Cement degradation was predominantly identified to be a result of alkali phosphate dissolution in conjunction with dissolution of phytic acid – calcium complexes formed during setting. The high degradation speed with a mass loss of 35–63% over 28 days indicated their potential to be evaluated further for orthopaedic and dental bone repair and regeneration applications as fully resorbable bone graft substitutes.